Helping, struggling or working? exploring labour migration trajectories of street vendors at a Havana Street Market in Windhoek, Namibia - Kharuchas, Anna Nalweendo (My University, 2020)
Set in Havana informal settlement, this study explores how Aawambo women street vendors at the Kabaka Street market reflect on their decisions to migrate to Windhoek, Namibia. Through its exploration of migrants’ emic perspectives, this study probes the economic rhetoric that labour migration can be reduced to ‘migrating to find work. ’It describes what ‘work’ subjectively entails for rural migrant women moving to Windhoek and what working in Windhoek means for migrants from their own vantage points. I use a qualitative research design highlighting migrant subjectivities to propose that economic triggers of migration are experienced in a multitude of ways mediated by factors such as gender and class. Embedded in the project is an investigation into migrants’ perceptions of work, Windhoek, places of origin and the role of migrant networks in their migration and work
A research report submitted to the Faculty of Humanities, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Migration and Displacement, 2020